Proceedings of the Workshop Modeling Wheat Response to High Temperature held in El Batán, Mexico, 19-21 June 2013 - Alderman, Phillip D.; Quilligan, Emma; Asseng, Senthold; Ewert, Frank; Reynolds, Matthew P. (International Maize and Wheat Improvement Center, 2013)
The abstracts herein are of presentations by experts participating in the workshop “Modeling Wheat Response to High Temperature”. Sponsored by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and in collaboration with the University of Florida, University of Bonn, and the Agricultural Model Intercomparison and Improvement Project (AgMIP).